Analisis Resepsi “Cyberbullying” Film Budi Pekerti (2023) pada Korban Cyberbullying - ABDURRAHIM DJALINS, RAZI; Bayu Widagdo, Muhammad; Ratri Rahmiaji, Lintang (Interaksi Online, 2024)
The increasing cases of cyberbullying on social media have become a serious concern. Film, as a mass communication medium, often portrays social realities, one of which is the film Budi Pekerti (2023) that addresses issues such as cyberbullying. This research aims to analyze how victims of cyberbullying interpret the messages conveyed regarding the phenomenon of cyberbullying in the film Budi Pekerti. Using Stuart Hall's Reception Theory, this study was conducted through a descriptive qualitative approach and reception analysis method. The researcher interviewed five informants who were victims of cyberbullying and had watched the film Budi Pekerti. The research findings show that the informants gave varied responses to the representation of cyberbullying in the film. Some informants were in a dominant-hegemonic position, where they fully accepted the moral messages conveyed by the film, especially regarding the serious impact of cyberbullying. On the other hand, there were informants in a negotiated position, where they accepted part of the message but with negotiation based on their personal experiences as victims. Lastly, there were also those in an oppositional position, rejecting the message because they felt the representation of cyberbullying victims in the film was not entirely relevant to their experiences. In conclusion, the film Budi Pekerti is generally considered capable of depicting cyberbullying from several aspects, although each informant's interpretation is influenced by social, cultural, and personal factors.